Impacts of Prolonged Waterlogging on Educational Continuity at Schools in Peri-Urban Areas of Dhaka, Bangladesh (The Dhaka University Journal of Earth and Environmental Sciences, 2021)
The purpose of the paper is to explore the massive impediments and challenges to continuing school education posed to school stakeholders due to protracted waterlogging in the peri-urban areas of Dhaka, Bangladesh. The primary data were collected through direct field observation, in-depth interviews, Focus Group Discussions (FGDs) and Key Informant Interviews in three academic institutions (primary school, high school, and higher secondary school/college) located in different peri-urban areas of Dhaka City. The research revealed that students, teachers, and families experience severe problems due to waterlogging every year. Academic activities are significantly interrupted and discontinued for long spells almost every year. In addition, students suffer from different types of diseases such as cold and fever, and water-borne and skin diseases. Books, clothes, and other belongings of students are often badly damaged. Ensuring Comprehensive School Safety (CSS), maintaining proper drainage system in and around the schools, and raising playgrounds, roads and plinths of buildings are some of the key steps that can contribute to better educational continuity in Dhaka’s schools.The Dhaka University Journal of Earth and Environmental Sciences, Vol. 9(1), 2020, P 13-23